Sleeping beauty or wide awake? - Stephen Sirris; Hans Austnaberg (Scandinavian Journal for Leadership & Theology, 2023)
This article studies mission within the context of traditional Nordic national churches. In the Evangelical Lutheran Church of Norway, a state church until 2012, eighty percent of all congregations have formal agreements with a mission organization to support a project abroad. Given their prevalence, these agreements need empirical investigation as they provide access to congregational understandings and their practicing of mission. From the perspective of missiology and organization theory, this article asks: What do the mission agreements accomplish in the congregations, and how do the congregations use the agreements? Based on interviews in six congregations, our analysis shows that the function of the agreements depends on the engagement of individual volunteers and employees. Engagement is high when projects are perceived as concrete and diaconal and are incorporated into congregations’ organizational structures and key activities. Mission is primarily understood as supporting projects in the global south and as sharing the Christian faith with churches in other countries.